Implementasi Metode Capital Asset Pricing Model (CAPM) Sebagai Penetapan Keputusan Investasi Saham Berdasarkan Undervalue dan Overvalue (Studi pada Sektor Perbankan di BEI Periode 2018-2022) - Lailia, Afdholul Nisfu; Mustaqim, M. (J-MAS (Jurnal Manajemen dan Sains), 2024)
The study aims to implement the CAPM (Capital Asset Pricing Model) method in undervalued and overvalued equity investment decisions in the banking sector in the EIB during the period 2018-2022. This research method uses descriptive quantitative methods. The data source used is secondary data of the closing price per month of the Bank listed on the Indonesian Stock Exchange and the Financial Services Authority during the period June 2018 s/d December 2022. Sampling using purposive sampling technique of 5 National Private Public Bank (BUSN) Devisa. The results of this study showed that of the 5 shares of the company that were the sample of the research, 1 company shares became undervalue, namely the company of the Bank of Jewelry (BNLI) where the rate of return of individual shares is greater than the expected return, while 4 other companies were included in the overvalue shares: Bank Central Asia (BBCA), Bank Pan Indonesia (PNBN), Bank CIMB Niaga (BNGA), and Bank OCBC NISP (NISP) whose individual share return rate is smaller than its expected return.